TEMPERATURE AND SOME BLOOD TRAITS RESPONSE TO ORGANIC AND INORGANIC SELENIUM ADDED TO THE BROILER DIET REARED AT HIGH TEMPERATURES - & Al-Hassani, Ali (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2020)
This study was conducted at the poultry farm -Animal Production Department/ College of Agricultural Engineering Sciences- University of Baghdad, for the period from 2018/8/17 to 2018/9/28, in order to study the effect of adding inorganic and organic selenium to the broiler diets reared at high temperatures in the physiological performance. A 420 un-sexed chicks of breed (Ross 308) were used in the experiment as a one-day old and with weight rate of 36.4g. The chicks were distributed randomly and equally on 7 treatments, each one included 3 replicates at 20 chicks/replicate. The experiment included the following treatments : T1,T2, and T3 as organic selenium treatments which are selenomethionin with a concentration of 0.3, 0.6, and 0.9 mg/kg feed, respectively, and T4, T5, and T6 as inorganic selenium treatments in the form of Sodium Selenite compound at a concentrations of 0.3, 0.6, and 0.9 mg/kg feed, respectively, and T7 control treatment without any addition of selenium, while the chicks were bred at a high temperature rate of 22.5 - 43.9 ℃. Organic and inorganic Selenium have not shown a clear effect in reducing body temperature compared to the control treatment, as well as, a high significant decreasing in the blood Hematocrit and Hemoglobin concentration for inorganic Selenium treatments compared to the organic Selenium and control treatments. Finally, The results indicated that there were no significant differences in the cholesterol and glucose levels in blood of organic and inorganic Selenium and control treatments.